(untitled) - William Cameron Bowman (Oxford, London, 1980)
This is an exciting book by two unconvetional professors of pharmacology. It presents the subject in a balanced and well described context of chemistry, biochemistry, molecular biology, embryology, physiolgy, pathology, immunology, and so on. All components have been expanded, some, such as endocrinology, the chemotherapy of infections and of cancer, and pharmacokinetics, greatly so. In addition, the book includes drugs used in skin disorders, drugs of abuse and dependence, and pharmacologically active constituents of food. One of the problems of pharmacology is that the subject matter may be presented simply as boring lists of drugs and their properties. Such lists, in the form of pharmacopoeias, formularies and prescriber's handbooks, provide valuable and indeed essential repositoiries of information about drugs
Keywords: medicine - formulae, receips, prescribing,pharmacology,pharmacopoeias